2022
DOI: 10.3389/fmicb.2021.698638
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics Exhibit Strain-Specific Protective Effects in T84 Cells Challenged With Clostridioides difficile-Infected Fecal Water

Abstract: Clostridioides difficile infection (CDI) is frequently associated with intestinal injury and mucosal barrier dysfunction, leading to an inflammatory response involving neutrophil localization and upregulation of pro-inflammatory cytokines. The severity of clinical manifestations is associated with the extent of the immune response, which requires mitigation for better clinical management. Probiotics could play a protective role in this disorder due to their immunomodulatory ability in gastrointestinal disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 79 publications
0
5
0
Order By: Relevance
“…All serum samples were applied to the cytokine detection kit (Bio-Plex Pro™ Human Inflammation Panel 1, 37-Plex, Bio-Rad) for the levels of cytokines. The experiment and adjustment of instrument were conducted following manufacturer instructions ( 28 ); the results were obtained by Milliplex Analyzer (Luminex 200) ( Table S1 ). Both the samples, quality controls and standards, were detected in two duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…All serum samples were applied to the cytokine detection kit (Bio-Plex Pro™ Human Inflammation Panel 1, 37-Plex, Bio-Rad) for the levels of cytokines. The experiment and adjustment of instrument were conducted following manufacturer instructions ( 28 ); the results were obtained by Milliplex Analyzer (Luminex 200) ( Table S1 ). Both the samples, quality controls and standards, were detected in two duplicates.…”
Section: Methodsmentioning
confidence: 99%
“…To accept a probiotic as a functional ingredient, a complete genome sequence of a target microorganism should be analyzed to identify the phenotype and genotype of the strain. It is important to identify the genus and species of probiotic strain because probiotic effects result from strain‐specific probiotic (Campana et al, 2017 ; Gaisawat et al, 2021 ; Kekkonen et al, 2008 ). A total of 19 types of probiotic species, which consist of five genera ( Lactobacillus, Lactococcus, Streptococcus, Bifidobacterium , and Enterococcus ), have been approved as probiotics by the MFDS of Korea, based on WHO/FAO guidelines (Kim et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, S. boulardii down-regulated eDNA in the C. difficile biofilm matrix through ‘cell-to-cell’ direct contact to inhibit the formation of the biofilm of C. difficile , which ultimately killed C. difficile and prevented recurrent infections. 35,36 However, there are individual clinical outcomes that are not ideal. Thomas et al found that L. rhamnosus GG did not reduce the rate of diarrhea.…”
Section: Order Of Priority In the Combination Of Bacteria And Drugmentioning
confidence: 99%